LEGAL CERTAINTY OF LAND GRANTS OF EX-USE RIGHTS ACCORDING TO LAW NUMBER 5 OF 1960 AND THE THEORY OF MILK AL-DAULAH - Sri Deviana Siska; Nurdin Bakri; Safira Mustaqilla (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study examines the legal uncertainty regarding the management of land previously under the Right to Cultivate (HGU) granted to PT Cemerlang Abadi in Babahrot District, Aceh, which presents a significant issue. Although the land has been utilised by around a thousand households for agricultural purposes, the government has not provided official certificates as legal proof of ownership. The slow administrative process and land redistribution by the Aceh government and the Southwest Aceh District Government contradict the principle of legal certainty as stipulated in Law No. 5 of 1960 on Basic Agrarian Regulations (UUPA). From an Islamic legal perspective, the land in question is a public asset that must be managed for the welfare of the people. This uncertainty poses potential social, economic, and legal risks, including future disputes. Therefore, concrete steps are needed, such as expediting data collection, issuing certificates, and providing legal education to the public. Addressing this issue would reflect social justice and the government's commitment to implementing fair and sustainable agrarian principles.